The Impact of WHO Essential Medicines Policies on Inappropriate Use of Antibiotics. - Kathleen Anne Holloway; Laura Rosella; David Henry (PLoS ONE)
Background Inappropriate overuse of antibiotics contributes to antimicrobial resistance (AMR), yet policy implementation to reduce inappropriate antibiotic use is poor in low and middle-income countries. Aims To determine whether public sector inappropriate antibiotic use is lower in countries reporting implementation of selected essential medicines policies. Materials and methods Results from independently conducted antibiotic use surveys in countries that did, and did not report implementation of policies to reduce inappropriate antibiotic prescribing, were compared. Survey data on four validated indicators of inappropriate antibiotic use and 16 self-reported policy implementation variables from WHO databases were extracted. The average difference for indicators between countries reporting versus not reporting implementation of specific policies was calculated. For 16 selected policies we regressed the four antibiotic use variables on the numbers of policies the countries reported implementing. Results Data were available for 55 countries. Of 16 policies studied, four (having a national Ministry of Health unit on promoting rational use of medicines, a national drug information centre and provincial and hospital drugs and therapeutics committees) were associated with statistically significant reductions in antibiotic use of ≥20% in upper respiratory infection (URTI). A national strategy to contain antibiotic resistance was associated with a 30% reduction in use of antibiotics in acute diarrheal illness. Policies seemed to be associated with greater effects in antibiotic use for URTI and diarrhea compared with antibiotic use in all patients. There were negative correlations between the numbers of policies reported implemented and the percentage of acute diarrhoea cases treated with antibiotics (r = -0.484, p = 0.007) and the percentage of URTI cases treated with antibiotics (r = -0.472, p = 0.005). Major study limitations were the reliance on self-reported policy implementation data and antibiotic use data from linited surveys. Conclusions Selected essential medicines policies were associated with lower antibiotic use in low and middle income countries.